Morphological Characteristics and Abundance of Bacteria in Fried Snack Foods from the Pujasera Canteen, Universitas Pattimura, and Fungi in Spoiled Fruits from Mardika Market, Ambon - Pattipeilohy, Merry; Mahulette, Ferymon; Pelamonia, Alamanda (RUMPHIUS, 2026)
This study investigated the morphological characteristics and abundance of bacteria and fungi isolated from fried snack foods and spoiled fruits. Bacterial isolates were obtained from bakwan, batagor, and stuffed tofu, while fungal isolates were recovered from spoiled mango, banana, and papaya. Culture-based methods were employed to characterize macroscopic colony morphology and to quantify microbial abundance using the Total Plate Count (TPC) method. The results revealed distinct dominance patterns across different food types. In fried snacks, isolates BKK3, BTK2, and STK5 exhibited the highest TPC values, reaching up to 10⁷ CFU/g, indicating substantial post-processing bacterial contamination. In contrast, spoiled fruits were predominantly colonized by fungal isolates MGK3, BNK3, and PPK4, with TPC values also reaching 10⁷ CFU/g. These fungal isolates displayed typical filamentous mold characteristics, including white-to-green mycelia, granular to rugose textures, and radial and concentric growth patterns. This comparative analysis within a unified study framework demonstrates that difference in food type and intrinsic characteristics-namely ready-to-eat processed products with high environmental exposure versus fresh fruit tissues rich in nutrients and simple sugars-shape contrasting microbial dominance patterns. Fried snacks were primarily dominated by post-processing bacterial contaminants, whereas spoiled fruits were characterized by saprophytic fungal predominance. These findings highlight the critical role of physicochemical properties and handling conditions in determining microbial community dynamics and provide a conceptual basis for microbiological risk assessment in street-vended and fresh food systems. Practically, the results underscore the importance of hygiene control and post-processing management to mitigate microbial hazards and potential mycotoxin risks.